The Role of NLRP3 Inflammasome Activation in the Epithelial to Mesenchymal Transition Process During the Fibrosis - Alyaseer, Amani Abraheem Alsadiq; de Lima, Murilo Henrique Saturnino; Braga, Tarcio Teodoro (Frontiers in Immunology, 2020)
Fibrosis is considered a complex tissue damage commonly present in the end stage of many diseases. It is also related to a high percentage of death; whose predominant characteristics are the excessive and abnormal deposition of fibroblasts and myofibroblasts -derived extracellular matrix (ECM) components. Epithelial-to-mesenchymal transition (EMT), a process in which epithelial cells gradually change to mesenchymal ones, is a major contributor in the pathogenesis of fibrosis. The key mediator of EMT is a multifunctional cytokine called transforming growth factor-β (TGF-β) once it acts as the main inducer of the ECM assembly and remodeling through the phosphorylation of Smad2/3, which ultimately will form a complex with Smad4 and translocate into the nucleus. On the other hand, the bone morphogenic protein-7 (BMP-7), a member of the TGF family, reverses EMT by directly counteracting TGF-β induced Smad-dependent cell signaling. NLRP3 (NACHT, LRR and PYD domains-containing protein 3), in turn, acts as cytosolic sensors of microbial and self-derived molecules and forms an immune complex called inflammasome in the context of inflammatory commitments. NLRP3 inflammasome assembly is triggered by extracellular ATP, reactive oxygen species (ROS), potassium efflux, calcium misbalance, and lysosome disruption. Due to its involvement in multiple diseases, NLRP3 has become one of the most studied pattern-recognition receptors (PRRs). Nevertheless, the role of NLRP3 in fibrosis development has not been completely elucidated. In this review, we described the relation of the previously mentioned fibrosis pathway with the NLRP3 inflammasome complex formation, especially those EMT-related pathways. For now, it is suggested that the EMT happens independently from the oligomerization of the whole inflammasome complex, just requiring the presence of the NLRP3 receptor and the ASC protein to trigger the EMT events, and we will present different researches that give controversial point of views.